Investigation of the electrochemical reactions at a limited-contact La1-xSrxMnO3/Y-doped ZrO2 interface with a rod-type ionic-probe - Ji, Ho-Il; Hong, Jongsup; Yoon, Kyung Joong; Son, Ji-Won; Kim, Byung-Kook; Lee, Hae-Weon; Lee, Jong-Ho (ELSEVIER SCIENCE BV, 2016)
A more quantitatively controllable triple phase boundary (TPB) of a lanthanum strontium manganite/yttria-stabilized zirconia (LSM/YSZ) interface was constructed by using an YSZ ionic probe with well-defined dimensions. A bar-shaped, dense YSZ sintered body was employed as an ionic probe and embedded in the pellet-shaped, dense LSM bulk. The TPB length of the LSM/YSZ interface can be simply determined from the circumference of the YSZ bars. To identify the reaction mechanism of the oxygen reduction reaction (ORR) at the TPB of the LSM/YSZ interface, limited-contact AC impedance spectros-copy was used; this distinguished the LSM/YSZ interface related polarization from other polarizations present in the Pt/LSM/YSZ/Pt electrochemical cell. By analyzing the electrode-related polarizations in the electrochemical cell with the geometrically quantified YSZ ionic probe, the rate determining step of the ORR was the diffusion of adsorbed oxygen along the LSM bulk surface. In this paper, emphasis is placed on the experimental versatility and the limitations of our designed electrochemical analysis with bar shaped ionic probes. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: OXIDE FUEL-CELLS; SR-DOPED LAMNO3; YTTRIA-STABILIZED ZIRCONIA; AC-IMPEDANCE SPECTROSCOPY; EXPERIMENTAL LIMITATIONS; REFERENCE ELECTRODE; 3-POINT MEASUREMENTS; GEOMETRY DEPENDENCE; LANTHANUM MANGANITE; COMPOSITE CATHODES